Strategi Komunikasi Lembaga Konservasi Alam Dalam Menjalankan Program Pemberdayaan Masyarakat - Novin Farid Setyo Wibowo; Moch Fuad Nasvian (Sospol : Jurnal Sosial Politik, 2022)
The Foundation of Bhakti Alam Sendang Biru successfully developed conservation-based tourism in the most significant coastal area in Malang Regency. The foundation owned good communication with the society and slowly reduced the conflict among the community. Based on the context of regional tourism governance, this collaboration process requires effective communication strategies in carrying out the program to create synergy both between the management and the public. So it is interesting to explain the foundation's communication strategy to achieve a shared vision. It uses interviews and documentation as the primary data collection. The subject of this research is the foundation and internal and external stakeholders. The communication strategy carried out by the Foundation is to use a family approach by prioritizing personal and communal solutions. The Foundation also establishes two-way communication with community relations guidelines and promotes collaboration based on equal partnerships with the surrounding community. In planning activities, the Foundation always involves the community in a participatory manner. The communication strategy applied in carrying out the community empowerment program is by determining the right communicator, then the communication media used, the type of issue being communicated and the appropriate communicant. Through this strategy that has been implemented, there is community involvement in various aspects in supporting the Foundation's programs, either directly or indirectly. The community does not feel that they are merely objects but can take on the role of subjects who can jointly carry out community empowerment programs.